Idarah al-Bi’ah al-Lughawiyah al-Arabiyah ‘Abra al-Taqyim al-Mutaqamil: Dirasah Halah li Hukumah al-Bi’ah al-Lughawiyah fi Mahad Islami bi Indonesia / Managing Arabic Language Environment through Integrated Assessment: A Case Study of Institutional Language Governance in an Indonesian Islamic Boarding School - Mhd Firdaus Lubis; Moh. Ainin; Mohammed Abdulaziz Mohammed AhmedEltigani (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
This study examines the management of the Arabic language environment and the implementation of an integrated assessment system at Ma’had At-Tibyan to enhance students’ communication skills. Employing a qualitative descriptive-analytical approach, data were collected through participatory observation, semi-structured interviews, and analysis of official documents, focusing on academic and extracurricular activities, institutional policies, and the application of assessment tools including direct observation, portfolios, practical tests, and peer feedback. Findings indicate that systematic management of the Arabic language environment comprising daily supervision, documentation of language violations, continuous reminders, structured disciplinary measures, and student participation as monitors, creates a consistent Arabic language culture, improves linguistic discipline, and strengthens speaking skills, self-confidence, and collective responsibility. The study provides a practical and conceptual framework for institutions seeking to integrate language environment management with comprehensive assessment, offering strategies to foster sustainable language use and communicative competence in Islamic educational settings.تستعرض هذه الدراسة إدارة البيئة اللغوية العربية وتطبيق نظام التقييم المتكامل في معهد التبيان بهدف تعزيز مهارات الاتصال لدى الطلاب. وقد اعتمد البحث على المنهج الوصفي التحليلي النوعي، حيث جُمعت البيانات من خلال الملاحظة المشاركة، والمقابلات شبه المنظمة، وتحليل الوثائق الرسمية، مع التركيز على الأنشطة الأكاديمية واللاصفية، والسياسات المؤسسية، وتطبيق أدوات التقييم بما في ذلك الملاحظة المباشرة، والمحافظ التعليمية، والاختبارات العملية، والتغذية الراجعة بين الأقران. أظهرت النتائج أن الإدارة المنهجية للبيئة اللغوية، بما يشمل الإشراف اليومي، وتوثيق المخالفات اللغوية، والتذكير المستمر، وتطبيق العقوبات التربوية المنظمة، وإشراك الطلاب كمراقبين، تُسهم في ترسيخ ثقافة استخدام اللغة العربية بشكل مستمر، وتعزيز الانضباط اللغوي، وتنمية مهارات التحدث، والثقة بالنفس، والمسؤولية الجماعية. توفر الدراسة إطارًا مفاهيميًا وعمليًا للمؤسسات التعليمية التي تسعى لدمج إدارة البيئة اللغوية مع التقييم الشامل، بما يدعم الاستخدام المستدام للغة والكفاءة التواصلية لدى المتعلمين في السياق التعليمي الإسلامي.